Exit of Entrepreneurs from Business: Reasons and Strategies - Pinkovetskaia, Iuliia; Schennikova, Natalya V.; Kryukova, Liudmila I. (Journal of History Culture and Art Research, 2020)
Cessation of business has received insufficient attention in the works of domestic and foreign scientists. However, sooner or later, each entrepreneur ceases to operate. The purpose of the study is to analyze the main reasons and ways of cessation of business, as well as assess shares of exit from business for certain reasons in economically developed countries. As the initial data, we used the results of the Global Entrepreneurship Monitoring Project for 2018, as well as the data presented in scientific publications. In the process of the study, a classification of the reasons for cessation of business has been proposed and the values of indicators characterizing these reasons have been estimated. Business exit strategies based on various options, forms and methods for implementing relevant processes have been considered. Originality and scientific novelty of the study: it shows that in most economically developed countries exogenous causes do not have a big impact on entrepreneurs to terminate business; entrepreneurial activity cessation is largely due to endogenous and personal reasons; every thirteenth entrepreneur goes out of business with the aim of turning assets accumulated in the course of business activity into cash resources. The study is aimed at understanding the reasons and strategies of cessation of business. It has scientific and practical significance, because it offers new data about peculiar features of entrepreneurial activity termination, as well as the share of certain reasons for business termination. The data is of interest to entrepreneurs, as well as government agencies and other institutions responsible for making plans, programs and forecasts for the development of the business sector. This article continues the discussion on the issue of termination of business.